Estudo comparativo das propriedades fundamentais das redes de polipropileno usadas no tratamento da incontinência urinária de esforço - Afonso, José Sebastião [UNIFESP] (2008)
Objective: With the aim of understanding what distinguishes the different polypropylene meshes, used for the treatment of the stress urinary incontinence (SUI), we investigated their fundamental properties. Methods: Five different mesh types were tested. The mechanical methods used consisted on uniaxial tension test (tensile stiffness) and tape ring tests, experimental continuous compression of the mesh loops (flexural stiffness). The chemical tests performed were differential scanning calorimetry (DSC), microtomography and infrared (FTIR). Furthermore, the geometry (electronic microscopy) and linear density (pyknometer) of the meshes were investigated. Results: The most significant difference of tensile stiffness behaviour appears between Aris™ and TVTO™. From the analysis of the experimental data, we divided the flexural stiffness in two main groups. The first group includes Auto Suture™ and Aris™ meshes. These meshes seem to have a similar flexural behaviour. The second group includes TVTO™, Uretex™ and Avaulta™. The difference between these two groups is clear when comparing TVTO™ and Aris™. The material of the meshes is the isotactic polypropylene. Aris™ mesh presented the smallest fiber diameter, linear density and level of crystallinity of all the meshes used for the treatment of the SUI. Conclusions: Concerning the polypropylene meshes used for the treatment of the SUI, this study shows that there are significant differences on the mechanical properties, and a direct relation between fiber diameter, linear density and level of crystallinity with flexural stiffness.